Acupuncture, Expertise and Cross-Cultural Medicine - Bivins, R. author. aut Link
XI, 263 p.
Keywords: Alternative medicine is a fifty billion dollar per year industry. But is it all nonsense? The Whole Story rounds up the latest evidence on the placebo effect, the randomized control trial, personalized genetic medicine, acupuncture, homeopathy, osteopathy and more. It reaches a provocative conclusion: alternative therapies' whole-body approach might be just what medicine really needs right now to help crack the tough, chronic conditions seemingly untouched by the revolutions of surgery, antiseptics, antibiotics, vaccines and molecular biology.